Bivalent circular RNA vaccines against porcine epidemic diarrhea virus and transmissible gastroenteritis virus - Zhang, Weibing; Wang, Lei; Chu, Liyu; Ma, Xu; Gao, Wenjing; Wu, Yarong; Qiao, Yongfeng; Wang, Xianjun; Zhao, Lu; Hu, Hong; Li, Xiaoyu; Zhang, Ding; et al. (Frontiers in Immunology, 2025)
Porcine Epidemic Diarrhea Virus (PEDV) and Transmissible Gastroenteritis Virus (TGEV) pose significant threats to neonatal piglets, leading to severe diarrhea and potentially lethal consequences. Beyond enforcing stringent biosecurity protocols, effective and safe vaccinations are crucial in mitigating the impact of these diseases. In this study, the PEDV S1 (PS1) and TGEV S1 (TS1) antigens were initially chosen as candidates for the development of circRNA vaccines. Recognizing the comparatively lower immunogenicity of the PS1 antigen in contrast to the TS1 antigen, we strategically conjugated the PS1 with the pig fragment crystallizable (Fc) region to form PS1F. Despite these efforts, the bivalent circRNA vaccine prepared using an equal amount of the circRNAPS1F and circRNATS1 mixture still led to a reduction in the antibody levels against PS1. Subsequent dosage optimization of these two circRNA vaccines resulted in the induction of comparable levels of antigen specific antibodies and T cell immunity. Furthermore, sequential vaccination regimen with bivalent circRNA vaccine and commercial inactivated vaccines (IAV) could elicit a predominantly Th1-driven antibody responses and effectively neutralize both PEDV and TGEV. Our findings not only provide a potential strategy for the development of bivalent or multivalent circRNA/mRNA-based vaccines but also highlight the promising application of sequential vaccination strategies within the swine industry.